Copper-catalyzed aerobic [3+2] : annulation of N-alkenyl amidines - Wang, Yi-Feng (2013)
A method for the synthesis of bi- and tricyclic amidines has been developed through copper-catalyzed aerobic [3+2]-annulation reaction of N-alkenyl amidines. These cyclic amidines could be converted into mono-benzyl-protected vicinal diamines by the reduction with aluminum hydride.